2013
DOI: 10.1111/pcmr.12170
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring melanomas in dogs as models for non‐UV pathways of human melanomas

Abstract: Spontaneously occurring melanomas are frequent in dogs. They appear at the same localizations as in humans, i.e. skin, mucosal sites, nail matrix and eyes. They display variable behaviors: tumors at oral localizations are more frequent and aggressive than at other anatomical sites. Interestingly, dog melanomas are associated with strong breed predispositions and overrepresentation of black-coated dogs. Epidemiological analysis of 2350 affected dogs showed that poodles are at high risk of developing oral melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
233
3
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(264 citation statements)
references
References 55 publications
13
233
3
15
Order By: Relevance
“…In humans, as described previously ( §2), germline mutations in CDKN2A can lead to familial melanoma with presentation at a young age regardless of sun exposure [42]. Dogs also develop melanoma, and similarly to all the other cancers discussed in this review, these melanocytic canine tumours will very closely resemble human melanoma, emphasizing the beneficial role of the canine preclinical model in studying both UV and non-UV pathways in melanoma [20,146]. Furthermore, the dog has been extremely useful for clinical trials and has contributed to a phase I study for DNA vaccination with xenogeneic human tyrosinase for advanced malignant melanoma [147][148][149][150][151].…”
Section: (E) Melanomamentioning
confidence: 89%
See 1 more Smart Citation
“…In humans, as described previously ( §2), germline mutations in CDKN2A can lead to familial melanoma with presentation at a young age regardless of sun exposure [42]. Dogs also develop melanoma, and similarly to all the other cancers discussed in this review, these melanocytic canine tumours will very closely resemble human melanoma, emphasizing the beneficial role of the canine preclinical model in studying both UV and non-UV pathways in melanoma [20,146]. Furthermore, the dog has been extremely useful for clinical trials and has contributed to a phase I study for DNA vaccination with xenogeneic human tyrosinase for advanced malignant melanoma [147][148][149][150][151].…”
Section: (E) Melanomamentioning
confidence: 89%
“…As Machiela & Chanock [37] discuss, although GRM4, which is involved in intracellular signalling and inhibition Table 1. Cancers associated with specific dog breeds (data from authors and [13,20] of the cyclic AMP signalling cascade, was not found to be associated itself with canine osteosarcoma, GRIK4, another glutamate receptor, was significantly associated with osteosarcoma risk in greyhounds; also, the SNPs close to GRM4 were fixed in Rottweilers with osteosarcoma [53]. This comparative approach may provide novel insight and validation of signalling pathways associated with osteosarcoma risk in both humans and dogs.…”
Section: Germline and Cancer Riskmentioning
confidence: 99%
“…En près de cinq ans, nous avons caractérisé différents types de méla-nomes canins et démontré leur homologie avec des types de mélanomes chez l'Homme : muqueux, acral, unguéal (ALM Acral lentiginous melanoma) (Gillard et al 2014). Ce travail montre que les mélanomes buccaux chez le chien dans des races prédisposées peuvent servir de modèles spontanés de mélanomes muqueux non-UV induits chez l'Homme, mais aussi de méla-nomes UV-induits.…”
Section: Discussion Et Perspectivesunclassified
“…To this end, many cancers in dogs and cats seem remarkably stronger models for counterpart human tumors than currently available murine model systems. [123][124][125][126][127] This is likely due to a variety of reasons, including, but not limited to, extreme similarities in the biology of the tumors (chemoresistance, radioresistance, sharing metastatic phenotypes and site selectivity, and so forth), spontaneous syngeneic cancer (vs typically an induced and/or xenogeneic cancer in murine models), and finally that the dogs and cats that are spontaneously developing these tumors are outbred, immune competent, and live in the same environment as humans. This author ardently looks forward to the time when immunotherapy plays a significant role in the treatment and/ or prevention of cancer in human and veterinary patients.…”
Section: Cancer Vaccinesmentioning
confidence: 97%